1999
DOI: 10.1159/000016504
|View full text |Cite
|
Sign up to set email alerts
|

Caries and Fluorosis Prevalence in Communities with Different Concentrations of Fluoride in the Water

Abstract: The need to defluoridate and fluoridate the water supplies in areas with drinking water naturally containing above–optimal (≥2.5 mg/l) and suboptimal (≤0.3 mg/l) fluoride concentration and caries and fluorosis prevalence of 12–year–old schoolchildren were assessed in Italy. In the low–fluoride area, 48.4% children were caries–free (DMFT = 0) and the DMFT and DMFS were 1.5 and 2.6; in the high–fluoride area, 46.8% had a DMFT = 0 and the values of the indices were 1.4 and 1.6, respectively. Multiple logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
2
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 24 publications
5
33
2
5
Order By: Relevance
“…In this study also the Community Fluorosis Index (CFI) for all permanent teeth was significantly higher in the high-fluoride area, 0.8, than the value, 0.1, found in the low-fluoride community [23].…”
Section: /7contrasting
confidence: 41%
“…In this study also the Community Fluorosis Index (CFI) for all permanent teeth was significantly higher in the high-fluoride area, 0.8, than the value, 0.1, found in the low-fluoride community [23].…”
Section: /7contrasting
confidence: 41%
“…These data strongly suggest the presence of environmental circumstances, which could have determined these conditions: as a matter of fact, it was already noted in the past that people living close to Naples suffered from endemic dental fluorosis [17][18][19][20]. Studies carried out in some Italian regions some years ago have demonstrated that the Community Fluorosis Index for all permanent teeth is significantly higher in highfluoride area, 0.8, than the value, 0.1, found in the low-fluoride community, determining the necessity to defluoridate and fluoridate the water supplies in areas with drinking water naturally containing above-optimal (Z2.5 mg/l) and suboptimal (r0.3 mg/l) fluoride concentration [21]. As known, fluoride catalyzes the diffusion of calcium and phosphate into the tooth surface, which in turn remineralizes the crystalline structures in a dental cavity.…”
Section: Discussionmentioning
confidence: 92%
“…Pinto (1997) afirma que o quadro epidemiológico brasileiro, em termos de saúde bucal, reflete com nitidez algumas das principais características da nossa sociedade: economia não estável, agudas desigualdades salariais e sociais, sistema educacional com ênfase na formação de nível superior, produção agrícola voltada para a exportação, grande número de pessoas de baixa renda e em estado de pobreza relativa ou absoluta. As tendências mundiais em relação à saúde bucal demonstram o declínio na incidência e prevalên-cia de cárie (Murray, 1994) e o aumento da prevalência da fluorose (Angelillo et al, 1999); tais ocorrências não estão distribuídas de forma homogênea em toda a população. Há concentração da doença cárie e as necessidades de tratamento em uma pequena parcela da população (20-40%), sendo que a maior parte apresenta-se praticamente livre de cárie (40-60%), esta ocorrência é conhecida como "fenômeno da polarização".…”
Section: Introductionunclassified